2019
DOI: 10.21077/ijf.2019.66.3.88889-08
|View full text |Cite
|
Sign up to set email alerts
|

Feeding diets with graded levels of fermented soybean meal to Pacific whiteleg shrimp Penaeus vannamei (Boone, 1931): Effect on digestive enzymes, immune responses and carcass composition

Abstract: A 45-days indoor trial was performed to assess the effect of fermented soybean meal (FSBM) on digestive enzyme activity, immune responses and carcass composition of amino acids, fatty acids, and minerals in Penaeus vannamei (Boone, 1931). Five iso-nitrogenous diets were formulated by replacing fishmeal (w/w) with FSBM (200, 250, 300. 350 and 400 g kg-1). A total of 300 juveniles (3.08±0.07 g) were randomly distributed to the experimental tanks at the rate of twenty shrimp per tank with three replications for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…vannamei reared on diets comprising A . niger fermented peanuts, rapeseed and soybean meals did not differ significantly from those fed a control diet in terms of proximate, amino acid, fatty acid and minerals 164,165 . This is consistent with the findings of Sun et al 166 who fed fermented cottonseed meal to P .…”
Section: Challenges On Usage Of a Nigersupporting
confidence: 90%
See 1 more Smart Citation
“…vannamei reared on diets comprising A . niger fermented peanuts, rapeseed and soybean meals did not differ significantly from those fed a control diet in terms of proximate, amino acid, fatty acid and minerals 164,165 . This is consistent with the findings of Sun et al 166 who fed fermented cottonseed meal to P .…”
Section: Challenges On Usage Of a Nigersupporting
confidence: 90%
“…Our prior studies demonstrated that P. vannamei reared on diets comprising A. niger fermented peanuts, rapeseed and soybean meals did not differ significantly from those fed a control diet in terms of proximate, amino acid, fatty acid and minerals. 164,165 This is consistent with the findings of Sun et al 166 who fed fermented cottonseed meal to P. vannamei. Relatively higher survival was obtained with the A. niger fermented ingredients even at higher inclusion.…”
Section: Complication On the Health Statussupporting
confidence: 89%
“…(2016) found that the concentrations of free amino acids, which are related to good taste (i.e., umami and sweet), were increased in the carp muscle after feeding with thermophile-fermented compost. Jannathulla et al. (2019) also reported significant changes in eicosatetraenoic acid (C20:5) and docosahexaenoic acid (C22:6) contents of shrimp fed with different levels of fermented soybean meal.…”
Section: Introductionmentioning
confidence: 89%
“…The lipid classes such as phospholipids, triacylglycerides and cholesterol in shrimp were estimated by Fiske and Subbarow (1925), Rice (1970) and Parekh and Jung (1970) method, respectively in a UV-visible spectrophotometer (UV1800-Shimadzu, Japan). Fatty acid methyl esters were prepared according to Metcalfe et al (1966) and were subsequently injected into a gas chromatograph (GC-2014, Shimadzu) equipped with RTX-wax capillary column (100 m length × 0.25 mm I.D × 0.2 µm film thickness) and flame ionisation detector (FID) according to Jannathulla et al (2019a).…”
Section: Laboratory Analysismentioning
confidence: 99%